Politics and technology in the post-truth era - Visvizi, Anna, 1976-; Lytras, Miltiadis D., 1973- (Bingley, U.K. : Emerald Publishing Limited, 2019)
Advances in information and communication technology (ICT) have directly impacted the way in which politics operates today. Bringing together research on Europe, the US, South America, the Middle East, Asia and Africa, this book examines the relationship between ICT and politics in a global perspective.Technological innovations such as big data, data mining, sentiment analysis, cognitive computing, artificial intelligence, virtual reality, augmented reality, social media and blockchain technology are reshaping the way ICT intersects with politics and in this collection contributors examine these developments, demonstrating their impact on the political landscape. Chapters examine topics such as cyberwarfare and propaganda, post-Soviet space, Snowden, US national security, e-government, GDPR, democratization in Africa and internet freedom.Providing an overview of new research on the emerging relationship between the promise and potential inherent in ICT and its impact on politics, this edited collection will prove an invaluable text for students, researchers and practitioners working in the fields of Politics, International Relations and Computer Science.
Prelims -- Chapter 1: Politics and ICT: issues, challenges, developments -- Chapter 2: From the freedom of the press to the freedom of the internet: a new public sphere in the making? -- Chapter 3: Diffusion patterns of political content over social networks -- Chapter 4: Contemporary politics and society: social media and public engagement in Belarus -- Chapter 5: Modeling public mood and emotion: blog and news sentiment and politico-economic phenomena -- Chapter 6: Political campaigns, social media, and analytics: the case of the GDPR -- Chapter 7: Assessing compliance of open data in politics with European data protection regulation -- Chapter 8: ICT, politics, and cyber intelligence: revisiting the case of Snowden -- Chapter 9: Government surveillance, national security, and the American rights: using sentiment analysis to extract citizen opinions -- Chapter 10: Information security risks in the context of Russian propaganda in the CEE -- Chapter 11: The ICT and its uses: fighting corruption and promoting participatory democracy - the case of Romania -- Chapter 12: Virtual currencies in modern societies: challenges and opportunities -- Chapter 13: Digital diplomacy in practice: a case study of the western Balkan countries -- Chapter 14: Social media and the Brazilian politics: a close look at the different perspectives and "the Brazil I want" initiative -- Chapter 15: Evaluation of the National Open Government Data (OGD) portal of Saudi Arabia -- Chapter 16: E-government strategy and its impact on economic and social development in Saudi Arabia -- Chapter 17: Romancing top management: the politics of top management support in large information system projects -- Chapter 18: Trade in ICT, international economy, and politics -- Chapter 19: Conclusion: politics and ICT - taking stocks of the debate -- Index.
Includes index.
Print version record
Keywords: Information technology -- Political aspects; Technological innovations -- Political aspects; Political Science -- General; Politics & government